Corruption, Violence, And The Rule Of Law Affecting Regulatory Control: Forecast Evaluation - Arvian Triantoro; Khalid Zaman; Sriyanto Sriyanto; Hailan Salamun; Shabnam; Sasmoko; Yasinta Indrianti; Abdul Rashid Abdul Aziz; Mohd Khata Jabor (Publishing House of the Higher School of Economics, 2024)
Political challenges, unfairness, and dishonesty are the governing issues that need substantial reforms to improve the high regulatory quality standards. The study's objective is to examine the impact of corruption, violence, and the rule of law on Pakistan's regulatory control. The study used four forecasting techniques, i.e., Root Mean Square Error (RSER), Mean Absolute Error (MAE), Mean Absolute Percentage Error (MAPE), and Theil inequality coefficient, on the available data series from 1996–2019. The study first obtained the forecast factors of the stated variables by using the Vector Autoregressive (VAR) technique and then used these variables in the least-squares regression technique to obtain the forecast parameter estimates. The simulation results show that corruption, violence, and the rule of law would likely negatively affect the country's regulatory control. The ex-ante analysis shows that the corruption level increases sharply reaches its highest point, and becomes constant. The rule of law initially decreases and then begins to rise steeply. Regulatory control initially decreases and is likely to increase at a decreasing rate. Finally, political stability is likely to decrease over the time horizon. Innovation accounting matrix estimates show that corruption would likely change the country's regulatory control, followed by the rule of law and violence in the next ten years. The study is the first to explore the dynamics of governance indicators in an inter-temporal setting. The study concludes that the country should devise broad-based governance reform policies to eliminate the high incidence of corruption, violence, and injustice and move forward towards implementing regulatory control for sustained growth.